Impact of CR before and after allogeneic and autologous transplantation in multiple myeloma: results from the EBMT NMAM2000 prospective trial - Iacobelli, Simona; Schönland, Stefan; Hegenbart, Ute; Goldschmidt, Hartmut (Bone marrow transplantation, 2015)
Previous studies have shown that obtaining complete hematologic remission (CR) in multiple myeloma is an important predictor of PFS and OS. This applies both to autologous and allogeneic transplantation. However, the importance of CR obtained before vs after second transplant or following allogeneic vs autologous transplantation is not clear. We investigated the role of CR analyzing data from the EBMT-NMAM2000 interventional prospective study comparing tandem autologous/reduced intensity conditioning allogeneic transplantation (auto/RICallo) to autologous transplantation—single or double (auto/auto). Allocation to treatment was performed according to availability of a matched sibling donor. Cox regression and multi-state models were applied. The long-term probability of survival in CR was superior in auto/RICallo, both comparing groups according to treatment allocated at start (28.8 vs 11.4% at 60 months, P=0.0004) and according to actual administration of second transplant (25.6 vs 9.6% at 60 months, P=0.008). CR achieved before the second transplant was predictive for PFS (hazard ratio (HR)=0.44, P= 0.003) and OS (HR 0.51, P=0.047) irrespective of the type of second transplant. CR achieved after auto/RICallo was more beneficial for PFS (HR=0.53, P=0.027) than CR after auto/auto (HR=0.81, P=0.390), indicating a better durability of CR obtained after an allotransplant procedure.